Is resale needed in markets with refunds? Evidence from college football ticket sales - Drew Vollmer (U.S. Department of Justice, Antitrust Division, Economic Analysis Group (EAG), 2022)
When is resale valuable? And when can it be replaced with refunds? I study the performance of common reallocation mechanisms in perishable goods markets with demand uncertainty. Using primary and secondary market data on college football ticket sales, I design a structural model to evaluate the performance of resale, partial refunds, and a menu of refund contracts. In the model, consumers anticipate shocks when making initial purchases. After shocks are realized, they participate in an endogenous resale market. I find that refunds are more efficient than resale, but that resale is better for sellers and consumers than not reallocating.
Keywords: 330